In Defense of Discomfort: The Role of Challenging Emotions in the Growth Toward Self-Authorship on a Weekend Retreat. Issue 1 (2nd January 2019) - Dugas, Daryl; Geosling, Bobbi Jean; Shelton, Jeron
Abstract: This article explores the experiences of undergraduate students participating in a retreat providing guidance toward self-authorship. In post-retreat interviews, participants discussed their experiences of discomfort during the retreat and its importance to their personal growth. Sources of discomfort included inhabiting unfamiliar environments and roles, participating in small group processes, and experiencing unpleasant emotions. Following the retreat, participants linked these experiences with greater capacity for introspection and greater ability to assert themselves. Implications for fostering students' self-authorship are discussed, including the need for greater engagement with students' emotions and for college educators to reconsider their own relationship with discomfort.